Nutraceutical Potential of Saffron in Counteracting Lead-Induced Physiological and Biochemical Changes in Poultry: A Review - Amen, Sameerah H. (American Journal of Biodiversity, 2025)
Lead remains a major environmental hazard for chicken farmers, leading to oxidative stress and damage to other organs. It also impairs immunity and productivity of the flocks. Traditional methods for reducing lead toxicity are limited in their scope to offering any relief. Safe and natural alternatives are one such hopeful sign of solution. Saffron (Crocus sativus), a medicinal plant that is rich in bioactive compounds such as crocin, crocetin, safranal, and picrocrocin, has shown significant prospects as nutraceuticals. Experiments have shown that saffron supplementation improves the antioxidant defense system (SOD, CAT, GSH), reduces lipid peroxidation (MDA), protects liver and kidney functions, and improves hematological and immune responses in Pb exposed poultry. Furthermore, saffron improves growth performance, feed conversion rates, meat quality (texture and taste), and reproductive health, making it a potentially ideal addition to poultry diets as an ingredient that will help fatten the bottom line. Through repeated testing and observation, these areas have all been confirmed to boast better performance statistically than traditional feeds currently in use. Despite difficulties such as cost, availability, and constancy in dose, saffron and its by-products present a promising, safe way of trying to control heavy metal poisoning in poultry and thus protect animal welfare and productivity in farming.